2020
DOI: 10.1177/1524838020953099
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Against Women in the Arab Countries: A Systematic Review of Risk Factors

Abstract: Intimate partner violence (IPV) profoundly damages physical, sexual, reproductive, and psychological health, as well as social well-being of individuals and families. We sought in this systematic review to examine the risk factors according to the integrative ecological theoretical framework for IPV for women living in the Arab countries. We searched Embase, PubMed, PsycINFO, and SCOPUS, supplemented by hand searching of reference lists. A research strategy was developed and observational studies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 102 publications
1
34
0
Order By: Relevance
“…Regional and societal factors may further impact victims' and perpetrators' access to help resources. For instance, in many settings around the world, patriarchal views of the family, social norms, or geographical distance from professional and private support resources may offer potential explanations for the increased risk of IPV ( 1 , 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regional and societal factors may further impact victims' and perpetrators' access to help resources. For instance, in many settings around the world, patriarchal views of the family, social norms, or geographical distance from professional and private support resources may offer potential explanations for the increased risk of IPV ( 1 , 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabic speaking countries, too, women are expected to be demure and obedient to their husbands, who use violence against wives and women who do not adhere to the norm [ 109 ]. In Latin America and the Caribbean, people in rural areas and in disadvantaged groups tend to have favorable attitudes toward the use of IPVAW by a male in response to infidelity by his partner [ 110 ].…”
Section: The Psychosocial Impact Of Ipvaw In Social Ecological Perspe...mentioning
confidence: 99%
“…In fact, it was suggested that the likelihood of violence against women decreases as the amount of social support available to them increases (20) and vice versa (21). Women who have friends or family members available for support seem therefore less socially isolated and thus in turn better protected from victimization at the hands of their partner than women without such support systems (22,23). In addition, social isolation plays a major role in creating the structural dislocation of minorities and marginalized populations and the differential distribution of resources (i.e., social capital), which in turn could directly increase the risk for IPV victimization for individuals who face overlapping social discriminations due to their race, gender, class, etc.…”
Section: Social and Geographical Isolation And Ipvmentioning
confidence: 99%